2008
DOI: 10.1029/2006jb004501
|View full text |Cite
|
Sign up to set email alerts
|

A discrete element model for the development of compaction localization in granular rock

Abstract: [1] A discrete element model was developed to simulate the micromechanics of compaction localization in a granular rock. The rock was modeled as a bonded assembly of circular disks, and seven different distributions of radius were considered. To simulate grain crushing and pore collapse, an intragranular damage mechanism was introduced that allows for the shrinkage of a disk if one of its normal contact stresses attains a critical value. The model captures key attributes of failure mode and damage evolution as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 56 publications
(138 reference statements)
8
81
0
Order By: Relevance
“…Apart from differences in average contact length, which varies with grain size, composition and degree of cementation, one can again clearly distinguish Bentheim and Diemelstadt sandstones with nearly identical narrow contact length distribution, from the Rothbach sandstone which shows significantly broader distribution. As proxies for grain-scale heterogeneity, these statistics of CT-number and grain contact length strongly support the idea that discrete compaction bands are promoted in a relatively homogeneous granular material, in agreement with recent numerical simulations using network (KATSMAN et al, 2005) and discrete element (WANG et al, 2008) models. Vol.…”
Section: Microstructural Origin Of the Mechanical Anisotropysupporting
confidence: 88%
“…Apart from differences in average contact length, which varies with grain size, composition and degree of cementation, one can again clearly distinguish Bentheim and Diemelstadt sandstones with nearly identical narrow contact length distribution, from the Rothbach sandstone which shows significantly broader distribution. As proxies for grain-scale heterogeneity, these statistics of CT-number and grain contact length strongly support the idea that discrete compaction bands are promoted in a relatively homogeneous granular material, in agreement with recent numerical simulations using network (KATSMAN et al, 2005) and discrete element (WANG et al, 2008) models. Vol.…”
Section: Microstructural Origin Of the Mechanical Anisotropysupporting
confidence: 88%
“…The observation that many shear bands in the semibrittle faulting regime show relatively large offsets (with offset to length ratio of up to~3%; Table 2) suggests that the bands are long-lived. This inference agrees with permanent, mesoscale bands predicted from models where grain contacts lose shear strength once slip occurs (Wang et al, 2008;Zheng et al, 2016), but differs from short-lived bands shown in models where the once-slipped contacts regain the strength (Aharonov & Sparks, 2002).…”
Section: Role Of Mesoscale Shear Bands On Granular Deformationsupporting
confidence: 82%
“…[22][23][24][25][26][27] Moreover, DEM models provide an avenue to investigate the effect of microscopic properties on the macro-scale response, like role of grain interlocking on strength, 28 effect of porosity on the deformability and strength, 29,30 effect of pore size and pore distribution. 31 The advantage of DEM over other continuum methods is its ability to explicitly model the initiation and propagation of cracks from micro-scale to macro-scale without applying complex constitutive laws.…”
Section: Numerical Methodologiesmentioning
confidence: 99%